PREVENTION OF CORRUPTION IN PUBLIC AUTHORITIES IN THE CONTEXT OF ECONOMIC SECURITY - KOSACH, Irina (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article provides an analysis of the current state of legal regulation of state administration regarding the prevention of corruption in state authorities in the context of economic security under martial law. Thus, one of the most important tasks of state administration in preventing corruption in public authorities is that the state must provide "legal security" to all its citizens, and this may require the introduction of temporary restrictions on the actions of certain normative legal acts regulating the issue of preventing corruption. The introduction of martial law and the relaxation of anti-corruption legislation can also lead to an increase in the risk of corruption, as such a situation is often accompanied by aggravation of the socio-economic situation and an increase in the susceptibility of citizens to various types of illegal activities. Therefore, it is important to ensure effective control over the activities of state bodies that ensure security in the conditions of martial law, and to implement preventive measures to prevent corruption in these bodies. Electronic declaration is considered one of the important tools for preventing corruption in the public sector. It is also characterized as an "anti-corruption declaration", based on the totality of all forms of legal consolidation and organizational support of universally binding rules of conduct in the totality of their interrelationships, through which prescriptions are objectified that determine the method of checking the integrity of authorized persons through the performance of duty from the declaration The priority of ensuring effective state administration in preventing corruption in order to preserve citizens' trust in state institutions and maintain social stability is indicated. It is argued that one of the important components of the fight against corruption in Ukraine today is the declaration of the income of officials. The directions of state administration regarding the prevention of corruption in state authorities in the conditions of martial law have been determined.
Keywords: public administration; prevention of corruption; state authorities; economic security